Lesiones histopatológicas en 12 casos de intoxicación por Vicia villosa. - Aguirre Castro, Laura Sabrina; Canton, German Jose; Morrell, Eleonora Lidia; Colque Caro, Luis Adrián; Sandoval, Gabriela Virginia; Medina, Diego M.; Avellaneda Cáceres, Agustín; Micheloud, Juan Francisco (EEA Balcarce, INTA, 2022)
Poster